Avaliação do desempenho do ozônio e do cloro na remoção do fármaco ácido mefenâmico solúvel em água - Tuha, Tatiane Arissa [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The contamination of the environment by pharmaceutical compounds has become a great concern due to the negative impacts they can possibly cause to humans, or to aquatic and terrestrial organisms. Different options of water treatments to remove this variety of pollutant are a matter of interest, given that conventional treatments used in wastewater treatment plants (WTP) are not efficient, and the detection of pharmaceuticals substances have been reported in several aqueous matrices, such as sewage, effluents from WTP, surface and groundwater, and even tap water. For these reasons, this study evaluates the oxidation performance by ozone and chlorine in the removal of soluble mefenamic acid (MEFS) in water. Previously, it was necessary to investigate the use of surfactants (Tween 80, Extran and common detergent) in the concentration of 1% (v/v) to increase the solubility of mefenamic acid in water, being chosen the addition of Extran 1% (v/v) surfactant in samples. Then, oxidation experiments were carried out in bench scale, testing different doses of ozone (8,17 mg/L; 10,21 mg/L; 20,42 mg/L; 29,61 mg/L; 40,03 mg/L; 50,04 mg/L; 60,05 mg/L and 70,00 mg/L) and chlorine (10,21 mg/L; 20,42 mg/L; 29,61 mg/L; 40,03 mg/L; 50,04 mg/L and 60,05 mg/L), with oxidation time of three minutes and neutral pH.. The quantification analysis of the drug were conducted by high performance liquid chromatography (HPLC). The results shows that the removal efficiency is increased along with the increment of the applied dose of oxidant. However, in higher doses (40,03 mg/L; 50,04 mg/L; 60,05 mg/L for both, and 70,00 mg/L for ozone) the efficiency is limited and tends to plateau, near 60% for ozone and close to 46% for chlorine, possibly because of the addition of the surfactant Extran 1% (v/v). In conclusion, both treatments showed removal potential of MEFS and the results shows a higher efficiency by...

A contaminação do meio ambiente por compostos farmacêuticos tem se tornado motivo de preocupação, devido aos impactos negativos que podem causar em humanos, e em organismos aquáticos e terrestres. Diferentes opções de tratamento de águas para a remoção desse tipo de poluente são de grande interesse, dado que tratamentos convencionais empregados em estações de tratamento de esgoto (ETEs) não são eficientes, e que existem relatos de detecção de substâncias farmacêuticas em diferentes fontes, como esgotos, efluentes de ETEs, águas superficiais e subterrâneas, e inclusive água de abastecimento. Por essas razões, esse trabalho avalia o desempenho da oxidação via ozônio e cloro na remoção do fármaco ácido mefenâmico solúvel (MEFS) em água. Antes foi necessário investigar o uso dos surfactantes Tween 80, Extran e detergente comum na concentração de 1% (v/v) para o aumentar a solubilidade do ácido mefenâmico em água, sendo escolhido a adição do surfactante Extran 1% (v/v) nas amostras. Então, foram realizados ensaios de oxidação em escala de bancada, testando diferentes doses de ozônio (8,17 mg/L; 10,21 mg/L; 20,42 mg/L; 29,61 mg/L; 40,03 mg/L; 50,04 mg/L; 60,05 mg/L e 70,00 mg/L) e cloro (10,21 mg/L; 20,42 mg/L; 29,61 mg/L; 40,03 mg/L; 50,04 mg/L e 60,05 mg/L), com tempo de oxidação de três minutos e pH neutro. As análises de quantificação do fármaco foram realizadas por cromatografia líquida de alta eficiência (HPLC). Os resultados mostram que a eficiência de remoção cresce com o aumento da dose de oxidante aplicada. Porém, nas doses mais altas (40,03 mg/L; 50,04 mg/L; 60,05 mg/L para ambos, e 70,00 mg/L para o ozônio) a eficiência é limitada e tende a estabilizar, em torno 60% para o ozônio e cerca de 46% para o cloro, possivelmente por causa da adição do surfactante Extran 1% (v/v). Em conclusão, ambos os tratamentos mostraram potencial para a...
Keywords: Abastecimento de água; Hidrologia; Água - Purificação; Fármacos; Cloro; Ozonio; Oxidação; Água - Poluição; Cromatografia líquida de alta eficiência